Pengaruh Literasi Keuangan Syariah Terhadap Minat Masyarakat Menggunakan Produk Pegadaian Syariah di Desa Aer Bale Kecamatan Sosa - Muhammad Amsal Nasution, Muhammad Amsal Nasution; Akhir Saleh Pulungan,; Mhd Toha Lubis, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The aim of this research is to find out how sharia financial literacy influences people's interest in using sharia pawnshop products in Aer Bale Village, Sosa District. This research uses a quantitative approach. The data collection technique used was a questionnaire. From a population of 105 people, a total of 31 samples can be obtained in this research using data analysis techniques using validity, reliability, correlation coefficient, determination coefficient and hypothesis testing.Based on the results of research carried out by researchers, it can be concluded that: (1) Sharia financial literacy is an individual's knowledge and ability to manage finances for the purpose of making decisions in accordance with the law and basic principles of sharia which will then benefit society in the future . In terms of sharia economic principles, sharia financial literacy provides several benefits: first, sharia financial literacy embedded in an individual will make the decision-making process based on sharia principles easier. Second, the more people invest and save, it is hoped that economic activity will run stably, because the sharia financial system strictly prohibits usury or interest, maysir (speculation), and also tadlis (fraud). Third, sharia financial literacy also provides benefits for the state, sharia financial institutions as financial service providers play a role in providing capital services in financial services and even sharia financial consultations. (2) The results of the T test research show that there is a significant influence between sharia financial literacy on people's interest in using sharia pawnshop products in Aer Bale village, Sosa District, as evidenced by the calculation results of the tcount > ttable value, namely 4.655 > 2.045. This means that partially the sharia financial literacy variable has a significant effect on people's interest in using sharia pawnshop products in Aer Bale village, Sosa District.